Community seed banks: farmers' platform for crop conservation and improvement - Tjikana, Thabo T.; Malueke, N.; Mokoena, M.; Vernooy, Ronnie; Sthapit, B.R. (GRAIN SA, 2016)
In South Africa, as elsewhere, the community systems that have maintained agrobiodiversity are increasingly coming under pressure from factors such as drought, crop failure and difficult storage conditions. As a result, the quantity of seed and number of plant varieties available to farmers for planting becomes negatively affected. With agricultural modernization, farmers are increasingly purchasing more of their seed requirements rendering local seed conservation less important. As commercial varieties replace older local varieties, the older varieties become increasingly unavailable in many communities. The Directorate Genetic Resources of the Department of Agriculture, Forestry and Fisheries, Bioversity International, and the Departments of Agriculture in Limpopo and Eastern Cape Provinces are working together to set up pilot community seed banks in Mutale and Joe Gcabi Municipalities respectively to guide the development of a national plan aimed to reverse the trend of biodiversity loss.